2013
DOI: 10.4103/2229-5194.126872
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of various irrigants against E. faecalis biofilm: An in vitro study

Abstract: Aim: This study evaluated the antimicrobial efficacy of irrigants during the cleaning and shaping of the canal system. This in vitro study evaluated quantitatively and qualitatively, the antimicrobial activity of 2% chlorhexidine gluconate, 5.25% sodium hypochlorite and MTAD against E. faecalis. Materials and Methods: Eighty freshly extracted human single-rooted mandibular premolars were selected and sectioned below the cement-enamel junction at 15 mm length. E. faecalis ATCC 29212 strain and clinical strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…However, 2% concentration of chlorhexidine is generally recommended in endodontic literature for the purpose of root canal irrigation. 30 In this study, Chlorhexidine demonstrated a broad spectrum antimicrobial action, which is similar to the results of the previous studies. 18,30,31 In the previous studies, minimal or no difference was observed when antimicrobial efficacy of NaOCl and 2% CHX against the root canal infection was compared.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, 2% concentration of chlorhexidine is generally recommended in endodontic literature for the purpose of root canal irrigation. 30 In this study, Chlorhexidine demonstrated a broad spectrum antimicrobial action, which is similar to the results of the previous studies. 18,30,31 In the previous studies, minimal or no difference was observed when antimicrobial efficacy of NaOCl and 2% CHX against the root canal infection was compared.…”
Section: Discussionsupporting
confidence: 91%
“…30 In this study, Chlorhexidine demonstrated a broad spectrum antimicrobial action, which is similar to the results of the previous studies. 18,30,31 In the previous studies, minimal or no difference was observed when antimicrobial efficacy of NaOCl and 2% CHX against the root canal infection was compared. 32,33 This is in accordance with this study as 2% chlorhexidine and 1% sodium hypochlorite showed no statistically significant difference in the reduction of the bacterial colonies (see Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…E. faecalis has certain factors of virulence including enzymes, cytolysin, and lipoteichoic acid. It was selected for this study because it has proven to be resistant to numerous antimicrobial agents and has been associated with resistant apical periodontitis [12]. The study was performed on root canals, which permits an improved observational study of the behavior of the bacteria in clinical conditions very similar to actual conditions.…”
Section: Discussionmentioning
confidence: 99%
“…faecalis was chosen as the test organism because it has been associated with persistent apical inflammation in clinical situations and is one of the intra-canal bacteria which are most resistant to elimination by disinfecting agent [16]. The prevalence of Enterococci, has been a conspicuous finding in a high percentage of rootcanal failures which has been attributed to its high resistance and its ability to survive as a single organism in monocultures The significant characteristics of Enterococci include their ability to grow in the range of 10°C-45°C and to survive around 30 min at 60°C, and at high salt concentrations of 6.5% saline as well as at extremely alkaline pH of up to 11 [17]. E. faecalis endures prolonged period of nutritional deprivation.…”
Section: Discussionmentioning
confidence: 99%